From exception to rule: The EU Trust Fund for Africa - David Kipp (Stiftung Wissenschaft und Politik (SWP), 2018)
Improving cooperation with countries of origin, transit and destination is central to the new European Agenda on Migration, launched by the European Commission in response to the 'refugee crisis' of 2015. The new EU Trust Fund (EUTF) for Africa finances projects in twenty-six African countries. Although initially conceived as a temporary emergency response, it has the potential to become a regular component of the EU's external migration policy, and can serve as a model for the systematic integration of the EU's migration interests into its external policy. However ideas diverge concerning the Fund's priorities. Internally, there is political pressure for the EU to concentrate on cooperation with transit countries in order to further reduce irregular migration to Europe. But narrowing the Fund's remit in that manner would be incompatible with the objectives of the Global Compacts on Migration and Refugees, which the United Nations adopted in December 2018. The German government should advocate for a comprehensive approach encompassing long-term support for countries of origin and destination. In order to improve the coherence of the EU's external migration policy, the vague goals of the EUTF need to be concretised and broken down into realistic sub-goals. Migration policy can only have sustainable effects if measures are embedded in a broader development agenda and take adequate consideration of the interests of African partner countries.
Keywords: 320